2021
DOI: 10.21203/rs.3.rs-342433/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High expression of RRM2 promotes the pathogenesis of malignant ovarian endometriosis.

Abstract: Objective: Our objective was to investigate the upregulated expression of ribonucleotide reductase M2 (RRM2) in the ectopic endometrium (EC) of ovarian endometriosis (OE) patients that may indicate malignant transformation. RRM2 may be used as a marker of OE, which contribute to the research of the mechanism of the malignant transformation of OE.Methods: The gene expression profiles of ovarian cancer and OE were downloaded from Gene Expression Omnibus (GEO), and a common hub gene, RRM2, was identified. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The expression and role of RRM2 have been reported in a variety of cancers [ 10 , 19 ]. However, its role in breast cancer and its mechanism are still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression and role of RRM2 have been reported in a variety of cancers [ 10 , 19 ]. However, its role in breast cancer and its mechanism are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that gene mutations and gene disorders are the main reasons leading to the occurrence and development of many cancers [ 4 ]. The differential expression of RRM2 is closely related to the occurrence, development, and prognosis of pancreatic cancer, gastric cancer, non-small cell lung cancer, liver cancer, malignant endometriosis, and other tumors [ 5 10 ]. Although targeted therapies, immunotherapy, chemotherapy, and radiotherapy are effective in the treatment of breast cancer, morbidity and mortality are still increasing.…”
Section: Introductionmentioning
confidence: 99%